HANDBOOK FOR ENGLISH TEACHERS - THOMAS BLACKBURN (LONDON METHUEM & CO LTD, 1966)
THIS BOOK HAVE BEEN CONCEIVED BY TEACHERS IN LONDON INSTITUTE OF EDUCATION WHO HAVE GIVEN SUCH AN INSPIRING LEAD IN THE THINKING.
Keywords: PRESNENTING POETRY